2021
DOI: 10.3389/fcell.2021.631063
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Intramedullary Injection of Mesenchymal Stem Cells During the Acute vs. Chronic Inflammatory Phase on Bone Healing in the Murine Continuous Polyethylene Particle Infusion Model

Abstract: Chronic inflammation is a common feature in many diseases of different organ systems, including bone. However, there are few interventions to mitigate chronic inflammation and preserve host tissue. Previous in vitro studies demonstrated that preconditioning of mesenchymal stem cells (pMSCs) using lipopolysaccharide and tumor necrosis factor-α polarized macrophages from a pro-inflammatory to an anti-inflammatory phenotype and increased osteogenesis compared to unaltered MSCs. In the current study, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 32 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…The increased pro-inflammatory M1 macrophage proportion and the decreased anti-inflammatory M2 macrophage proportion caused by cPE over a 3-week period was subsequently reduced by the local injection of MSCs and NF-κB sensing IL-4 over-expressing MSCs at harvest 3 weeks later. The increased TRAP positive osteoclast-like cell number, the lower ALP positive osteoblast-like area and BMD trend in the presence of cPE infusion further confirmed that the cPE could induce bone loss ( Lin et al, 2016 , 2017a ; Pajarinen et al, 2017 ; Utsunomiya et al, 2021a , b ). The injection of MSCs and NF-κB sensing IL-4 over-expressing MSCs reversed these findings in part.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…The increased pro-inflammatory M1 macrophage proportion and the decreased anti-inflammatory M2 macrophage proportion caused by cPE over a 3-week period was subsequently reduced by the local injection of MSCs and NF-κB sensing IL-4 over-expressing MSCs at harvest 3 weeks later. The increased TRAP positive osteoclast-like cell number, the lower ALP positive osteoblast-like area and BMD trend in the presence of cPE infusion further confirmed that the cPE could induce bone loss ( Lin et al, 2016 , 2017a ; Pajarinen et al, 2017 ; Utsunomiya et al, 2021a , b ). The injection of MSCs and NF-κB sensing IL-4 over-expressing MSCs reversed these findings in part.…”
Section: Discussionmentioning
confidence: 59%
“…The presence of cPE significantly reduced BMD in the control groups. Previous reports showed that injection of MSCs and preconditioning of MSCs during the chronic inflammation stage could increase the BMD in the presence of cPE ( Utsunomiya et al, 2021a ). In the current study, local injection of MSCs and NF-κB sensing IL-4 over-expressing MSCs also tended to increase BMD in the presence of cPE.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations